(Mis-)information technology: Internet use and perception of democracy in Africa - Joël Cariolle; Yasmine Elkhateeb; Mathilde Maurel (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
The Internet has significantly expanded worldwide, changing our relationship with the world, and the way we communicate, educate, and inform ourselves. Africa, despite having a very low number of fixed-broadband subscriptions for 100 inhabitants, has not escaped the Internet phenomenon, as the number of individuals with Internet access has risen from 2 in 2002 to 39.7 (per 100 inhabitants) in 2022. Similarly, the number of individuals with mobile- cellular telephone subscriptions has jumped from 12.4 in 2002 to 86.3 (per 100 inhabitants) in 2022 (ITU, 2022).
Keywords: D72; D83; L86; P16; 330; Internet news; democracy; Africa; Digital development; Digital technologies